The Association Between Masticatory Performance, Oral Health Status, and Dental Prostheses in Adults at a Dental Hospital in Jakarta - Ayub, Fakhrana Ariani; Gita, Farisza; Ariani, Nina (UI Scholars Hub, 2021)
Masticatory performance has been studied extensively in the past few decades. Age, gender, the number of teeth in occlusion, occlusal contact area, salivary flow, and neurophysiological deficits influence the masticatory process. The replacement of missing teeth with dental prostheses, whether fixed or removable, is often used to achieve an acceptable level of masticatory performance. Objective: The present study aimed to analyze the association between masticatory performance and age, gender, and oral health status based on the decayed, missing, and filled teeth (DMF-T) score, denture use, and denture condition in an adult population. Methods: This study included a total of 152 individuals (60 males and 92 females) aged 17 years or older (mean ± standard deviation: 33.4 ± 13.1 years). Masticatory performance was evaluated using color-changeable chewing gum. The chi-squared test was used to assess the association between masticatory performance and age, gender, DMF-T score, dental prosthesis use, and prosthesis condition. Results: Age (p=0.001), missing teeth (p=0.001), and prosthesis use (p=0.011) had significant relationships with masticatory performance. However, the correlations between masticatory performance and gender, tooth decay, fillings, and prosthesis condition were not statistically significant (p > 0.05). Conclusion: Age, missing teeth, and prostheses are strongly associated with masticatory performance.